2017
DOI: 10.1016/j.cub.2016.11.049
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Follows Repair Factor Depletion and Portends Genome Variation in Cancer Cells after Pore Migration

Abstract: Migration through micron-size constrictions has been seen to rupture the nucleus, release nuclear-localized GFP, and cause localized accumulations of ectopic 53BP1 – a DNA repair protein. Here, constricted migration of two human cancer cell types and primary mesenchymal stem cells (MSC) increases DNA breaks throughout the nucleoplasm as assessed by endogenous damage markers and by electrophoretic ‘comet’ measurements. Migration also causes multiple DNA repair proteins to segregate away from DNA, with cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
323
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 270 publications
(347 citation statements)
references
References 50 publications
24
323
0
Order By: Relevance
“…When MCF10A cells were subjected to migration through 3µm pores we observed cGAS localization to both micronuclei and nuclear blebs consistent with nuclear envelop disruption and transient DSB production (Extended data 4d and 4e) 20 . cGAS positivity of these subcellular structures still occurred in the presence of CDKi, demonstrating that mechanical nuclear rupture bypasses the need for mitotic progression.…”
mentioning
confidence: 58%
“…When MCF10A cells were subjected to migration through 3µm pores we observed cGAS localization to both micronuclei and nuclear blebs consistent with nuclear envelop disruption and transient DSB production (Extended data 4d and 4e) 20 . cGAS positivity of these subcellular structures still occurred in the presence of CDKi, demonstrating that mechanical nuclear rupture bypasses the need for mitotic progression.…”
mentioning
confidence: 58%
“…During interphase, cGAS can be rapidly detected at sites of NE rupture at the nuclear periphery, which is subsequently followed by the focal acquisition of DNA damage [43, 44]. Similar rupturing events were reported to promote genomic copy number aberrations [48], and cGAS has been shown to associate with condensed chromosomes after NE breakdown during mitosis [49]. Consistent with this, recent work confirmed that cGAS could indeed sense micronuclear DNAs exposed to the cytoplasm following micro-NE disruption as cytosolic self-DNA [50], although the downstream consequences on the micronuclear chromosome itself are unknown.…”
Section: Sources Of Micronuclear Dna Damagementioning
confidence: 92%
“…3740 Note that in the absence of CDK inhibitors, DNA-damaged cells acquire deformed polyploid nuclei. 41,42 In response to Shh-mediated developmental signals, NOTCH1/2 facilitate the clearance of the tumor suppressor Ptch1, the concurrent accumulation of the Shh signal-transducing protein encoded by SMO , and the increased downstream conversion of the proteins encoded by the oncogenes GLI1/3 into cell cycle transcriptional activators. 43,44 Note that Notch is critical for an Shh-induced medulloblastoma brain cancer tumor’s development.…”
Section: Astrocytoma Tumor-exclusive Genotype and Phenotypementioning
confidence: 99%